1990
DOI: 10.2105/ajph.80.11.1318
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a food use checklist for evaluation of community nutrition interventions.

Abstract: We developed a new dietary assessment instrument, the Food Behavior Checklist (FBC), which measures food use related to adopting lower-fat and higher-fiber diets. The FBC is a simplification of the 24-hour diet recall that consists of 19 simple yes/no questions about foods consumed during the previous day. To develop the FBC, an expert committee generated a list offoods based on our intervention program, and we used focus groups and randomdigit dialing pretests to refine the format and clarify items. To valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
5

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 12 publications
1
40
0
5
Order By: Relevance
“…Em seguida, o pesquisador perguntou explicitamente sobre o consumo dos alimentos de interesse (incluídos no questionário da PeNSE) no dia anterior (recordatório simplificado) à ligação desde a hora em que acordou até a hora em que foi dormir 17,28,29 . Adicionalmente, em cada entrevista, foi perguntado sobre a realização, no dia anterior, das atividades de interesse para os indicadores de rotinas alimentares (REFEIÇÃO, DESJEJUM e prática de comer enquanto estuda ou assiste à TV).…”
Section: Recordatório De 24 Horas (Método De Referência)unclassified
See 1 more Smart Citation
“…Em seguida, o pesquisador perguntou explicitamente sobre o consumo dos alimentos de interesse (incluídos no questionário da PeNSE) no dia anterior (recordatório simplificado) à ligação desde a hora em que acordou até a hora em que foi dormir 17,28,29 . Adicionalmente, em cada entrevista, foi perguntado sobre a realização, no dia anterior, das atividades de interesse para os indicadores de rotinas alimentares (REFEIÇÃO, DESJEJUM e prática de comer enquanto estuda ou assiste à TV).…”
Section: Recordatório De 24 Horas (Método De Referência)unclassified
“…O primeiro refere-se a dois estudos que validaram esse tipo de instrumento 28,29 e um estudo que o selecionou como método de referência para validar indicadores utilizados por sistema de vigilância específico para adolescente 17 . O segundo conjunto advém de análises preliminares do nosso estudo.…”
Section: Análise Dos Dadosunclassified
“…Intake measures need to be accurate yet practicable within the resources of the intervention work. Kristal et al (1990), for example, have developed a 'Short Dietary Questionnaire' which is reported to measure fat intake accurately; thorough validation of such measures would appear to be a useful investment of effort given the potential payoffs of their use in intervention work.…”
Section: W H a T A R E T H E I M P L I C A T I O N S F O R T H E P R mentioning
confidence: 99%
“…They are easy targets for criticism because they must navigate the often unclear tradeoffs between validity, reliability, response burden, and practicality in implementation. The procedures implemented by the USDA in developing the behavior checklist are in line with the recommendations of the literature (e.g., Contento, Randell, and Basch, 2002;Kristal et al, 1990) and there is some evidence that behavior checklist questions can correlate reasonably well with behavioral and some biological changes (e.g., Murphy et al, 2001). However, when there is interest in possibly multiple domains or constructs, the improvement in a particular domain could simply depend on the number or type of questions asked, as pointed out by a reviewer.…”
Section: Discussionmentioning
confidence: 62%